FUNCTION OF THE RIPE ROTTAN AS THE MATERIALS OF FIRE-MAKING: THE TRADITIONAL APPROACH IN LANI, PAPUA HIGHLAND - Napius Kogoya; Manase Halitopo (2024)
Lani tribe has many heritages to preserve such as traditional cook, tradition game, and the local fire-making etc. However, the local fire-making is very important to preserve to the next generation. Purpose of this research was to recognize the fire-making from the Lani tribe. The researcher took the data from elders who have grown up and the stakeholder in Lani Jaya. This research was done by using qualitative research. In collection the data the researcher did the observation, interview, and documentation. In analyzing data, the reseacher used the data condensation, data display, and verifying. All in all, the result are shown that there are some things used to design the fire making: Mbirim nggaganak wumbuk wolonak (dry rattan), Yibino nggaganak wumbuk wolonak (dry wild bamboo), Eyo Inar ogobak kirik wolonak (dry wood), Tor ogobak kirik wolonak (the dry clip wood), Mbree engga wumbuk wolonak (dry leaf), Pubu engga wumbuk wolonak (dry grass), Kani ebe ngaganak umbuk wolonak (dry wood), Kani apir wumbuk wolonak (dry stalk wood), Kani enggawak wumbuk wolonak (dry branch wood), Kami engga wumbuk wolonak (dry leaf wood)